2006
DOI: 10.1200/jco.2005.03.8224
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile–Defined Classification of Lung Adenocarcinoma Shows Close Relationship With Underlying Major Genetic Changes and Clinicopathologic Behaviors

Abstract: This study has shed light on heterogeneity in lung cancers, especially in adenocarcinomas, by establishing a molecularly, genetically, and clinically relevant, expression profile-defined classification. Future studies using independent patient cohorts are warranted to confirm the prognostic significance of EGFR mutations in TRU-type adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
284
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(307 citation statements)
references
References 25 publications
20
284
1
Order By: Relevance
“…Characterization of the 45-gene metastatic signature using gene ontology terms In order to gain functional insight into how the metastasis signature genes might contribute in the acquisition of metastatic potential in LNM35, we therefore employed our Gene Ontology (GO) term identifier of functions and other characteristics that are utilized in association with certain phenotypes of interest (Takeuchi et al, 2006). With this identifier, we found that GO terms related to four biological processes, three molecular functions and one cellular component were significantly more frequently observed than expected (Po0.005), when the frequency of a GO term appearing in the 45-gene metastatic signature was compared with that in the entire set of 8644 unique genes on the microarrays used in this study ( Table 2).…”
Section: Identification Of Genes Associated With the Acquisition Of Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterization of the 45-gene metastatic signature using gene ontology terms In order to gain functional insight into how the metastasis signature genes might contribute in the acquisition of metastatic potential in LNM35, we therefore employed our Gene Ontology (GO) term identifier of functions and other characteristics that are utilized in association with certain phenotypes of interest (Takeuchi et al, 2006). With this identifier, we found that GO terms related to four biological processes, three molecular functions and one cellular component were significantly more frequently observed than expected (Po0.005), when the frequency of a GO term appearing in the 45-gene metastatic signature was compared with that in the entire set of 8644 unique genes on the microarrays used in this study ( Table 2).…”
Section: Identification Of Genes Associated With the Acquisition Of Mmentioning
confidence: 99%
“…2000) analysis was employed to highlight functionally distinct biological features of a gene set associated with the acquisition of invasive and metastatic capabilities in LNM35, as described previously (Takeuchi et al, 2006). Briefly, database files used for this GO analysis were downloaded from the UniGene ftp site.…”
Section: Microarray Data Acquisition and Analysesmentioning
confidence: 99%
“…For survival analysis of LDHB gene expression, LDHB expression and survival data were previously published (Gene Expression Omnibus GSE11969; ref. 22). LDHB expression was mean-centered across all tumors then separated by above or below the mean.…”
Section: Survival Analysismentioning
confidence: 99%
“…Genetic alterations involved in the pathogenesis of lung cancer produce proteins involved in cell growth, invasion/ metastasis, differentiation, cell cycle processes, apoptosis and angiogenesis. Discovering these mechanisms and pathways will undoubtedly lead to new ways in dealing with prevention, early detection and therapy, for example, expression profiling can subclassify lung adenocarcinoma in terms of predicting length of survival [3].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic alterations involved in the pathogenesis of lung cancer produce proteins involved in cell growth, invasion/ metastasis, differentiation, cell cycle processes, apoptosis and angiogenesis. Discovering these mechanisms and pathways will undoubtedly lead to new ways in dealing with prevention, early detection and therapy, for example, expression profiling can subclassify lung adenocarcinoma in terms of predicting length of survival [3].A number of potential biomarkers have recently been identified, but currently, no satisfactory biomarkers are available to screen for lung cancer due to low specificity and sensitivity [4,5]. Lung cancer biomarkers have the potential to be involved in patient screening, monitoring of cancer progression, treatment response and as a predictive factor for Correspondence: Dr. Paul Dowling, The National Institute for Cellular Biotechnology, Dublin City University, Dublin 9, Ireland E-mail: paul.dowling@dcu.ie Fax: 1353-1-7005484…”
mentioning
confidence: 99%